Examination of the rheological properties of stirred joghurt during the long-term storage by using dynamic oscillation method - Milica Vilušić (Mljekarstvo)
In this work the rheological properties of stirred yoghurt during the longterm storage at 4 and 8°C were investigated. The optimal quantity of additives, in order to increase dry matter content (whole milk powder and whey protein-lactalbumin), was preliminary determined and the fermentation was performed. During 42 days, i.e., 1st, 7th, 14th, 21st, 28th, 35th and 42nd day of storage of stirred yoghurt, in refrigerator at 4 and 8°C, the changes of pH value, acidity and rheological properties by using of dynamic oscillation method were observed. Results of this work indicated that an addition of whole milk powder and whey protein have an influence on rheological properties of stirred yoghurt. The long-term storage of stirred yoghurt and the results of dynamic oscilations showed permanently higher G’storage (elasticity) modulus, where elastic properties of viscoelastic products dominate, in comparison with the G” loss (viscosity) modulus. Increased moduls of elasticy and viscosity, as function of time, permanently occurs at pH value 4.00 and lower, as an indication of alteration of long casein chains in the coagulum structure. Different temperatures of storage had no influence on changes of rheological properties of examinated types of stirred yoghur. The relation of above mentioned moduls of elasticy and viscosity kept the same increasing tendency.